2010
DOI: 10.1097/iae.0b013e3181e7978e
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Pilot Study of Systemic Immunosuppression in the Treatment of Age-Related Macular Degeneration With Choroidal Neovascularization

Abstract: Background Age-related macular degeneration remains the leading cause of irreversible blindness in the United States and the developed world. Intravitreal injections of anti–vascular endothelial growth factor (VEGF) medications have become standard of care for the treatment of the wet form of the disease. Recent reports have demonstrated an association with various immune factors. We aimed to investigate the effect of immunosuppressive therapy in the clinical course of the wet form of the disease. We compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…Inflammatory reactions are widely thought to be one of the initiating and /or promoting factors in CNV in AMD [56][57][58][59]. Recent studies on the role of chemokines and their receptors in CNV in AMD [60][61][62] indicate potential new avenues for exploration of chemokine targeting in search of AMD therapies.…”
Section: Il-4 Induces Secretion Of Ccl-11 and Ccl-26 But Not Ccl-24 Bmentioning
confidence: 99%
“…Inflammatory reactions are widely thought to be one of the initiating and /or promoting factors in CNV in AMD [56][57][58][59]. Recent studies on the role of chemokines and their receptors in CNV in AMD [60][61][62] indicate potential new avenues for exploration of chemokine targeting in search of AMD therapies.…”
Section: Il-4 Induces Secretion Of Ccl-11 and Ccl-26 But Not Ccl-24 Bmentioning
confidence: 99%
“…73,74 A recent pilot clinical trial appears to support this notion. 75 Cellular senescence is characterized by a hyper-secretory phenotype. [76][77][78] Also noteworthy, mTOR stimulates translation of HIF-1α.…”
mentioning
confidence: 99%
“…A randomized pilot study of systemic immunosuppresion with infliximab (3 mg/kg monthly for 6 months) as an adjuvant to anti-VEGF treatment did not appear to reduce the treatment burden of intravitreal anti-VEGF injections. 30 Rabbit models have shown that intravitreal adalimumab in doses up to 5 mg are safe. 14,15 Five patients with refractory cystoid macular edema secondary to noninfectious uveitis were treated with intravitreal adalimumab for 3 months with no apparent benefit.…”
Section: Discussionmentioning
confidence: 99%